Parameter uncertainty in policy planning models: Using portfolio management methods to choose optimal policies under world market volatility - A. Mukashov (Economic Analysis and Policy, 2023)
Even accurate and precisely specified models with excellent underlying data quality can be inhibited by parameter uncertainty that reflects uncertain factors. This paper suggests adopting portfolio management methods from finance in policy planning models as a practical tool for explicitly reckoning the parameter uncertainty when defining optimal policy. We demonstrate the approach in an economywide model that aims to find an optimal pro-poor agricultural value chain in Senegal under the world market uncertainty. We show that prioritizing the rice sector is the most effective policy in terms of expected policy return, but this policy is also associated with the highest risk, increasing poverty under unfavorable yet realistic scenarios. However, like diversified portfolios in finance, balancing rice promotion with support for other sectors can reduce risk at the cost of reduced expected policy return. The suggested methodology allows for explicit risk-based decision-making and can be used in policy prioritization models that cannot define robust optimal policy under standard parameter sensitivity analysis tests.
Keywords: 330